Ischemic necrosis of gastric stump: analysis of 1 case and statistical review - Estrugo, Roberto (Cirugía del Uruguay, 1979)
The author reports on a case of ischemic necrosis of gastric stump with reference t> its outstanding anatomical, etiopathogenic and therapeuticar characteristics. Considerable value is attached to drainage of operative field. Total gastrectomy is considered the safest procedure. The paper in,ludes an analysis of national case material and a bibliographic review of the subject.